Thermal buffering-controlled temperature variation between Mg–Al-rich rocks and migmatites - Samantha March; Martin Hand; Laura Morrissey; David Kelsey (Scientific Reports)
Abstract It is well recognised that endothermic processes such as dehydration and partial melting have the potential to exert measurable effects on the maximum temperatures reached in metamorphic rock systems. We show migmatitic metapelitic and mafic granulites record temperatures of ~ 820 °C, while spatially associated refractory Mg–Al-rich granulites record temperatures between 865 °C and > 920 °C. These thermally contrasting samples are separated by ~ 1500 m, with no apparent intervening faults or shear zones to explain the apparent difference in peak metamorphic conditions. Temperature versus enthalpy modelling of these samples along simple prograde P–T paths imply migmatisation slows the rate of temperature increase relative to rocks that do not melt. We speculate refractory rocks in the present study are created through early hydrothermal alteration and metamorphism, resulting in melt-resistant bulk compositions. There are many potential geological contexts where neighbouring rocks may have contrasting melt fertility; the deposition of a cover sequence, pre-metamorphic alteration, and the intrusion of igneous protoliths are all possibilities. With this in mind, variations in maximum modelled temperatures in granulite facies domains should be relatively common.